1997
DOI: 10.1002/(sici)1096-9861(19970929)386:3<422::aid-cne7>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of orbital and choroidal blood vessels by the pterygopalatine ganglion in pigeons

Abstract: Orbital and choroidal blood vessels in mammals are known to receive a parasympathetic innervation from the pterygopalatine ganglion, which appears to utilize vasoactive intestinal polypeptide (VIP) and nitric oxide (NO) to increase choroidal blood flow. The present studies were undertaken to elucidate the anatomical and neurotransmitter organization of the pterygopalatine ganglion input to orbital and choroidal blood vessels in pigeons. Single- or double-label immunohistochemistry were employed on paraformalde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…Choroidal blood vessels and NVSMC also receive a prominent innervation by cholinergic neurons in the ciliary ganglion (Meriney and Pilar 1987;De Stefano et al 1993;De Stefano and Mugnaini 1997a) and by nitrergic/VIP-ergic neurons in the pterygopalatine ganglion (Cuthbertson et al 1997). It remains to be established whether ICN are also intercalated in a parasympathetic pathway to the choroid, similar to their relationship to the sympathetic pathway.…”
Section: Functional Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Choroidal blood vessels and NVSMC also receive a prominent innervation by cholinergic neurons in the ciliary ganglion (Meriney and Pilar 1987;De Stefano et al 1993;De Stefano and Mugnaini 1997a) and by nitrergic/VIP-ergic neurons in the pterygopalatine ganglion (Cuthbertson et al 1997). It remains to be established whether ICN are also intercalated in a parasympathetic pathway to the choroid, similar to their relationship to the sympathetic pathway.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…However, they have only recently become amenable to closer scrutiny by virtue of their nitric oxide synthase (nNOS)/ NADPH-diaphorase (NADPH-d) reactivity (Bergua et al 1993;Flügel et al 1994;Cuthbertson et al 1997). Immunocytochemical and histochemical techniques have made apparent their abundance in humans and higher primates and their scarcity or even absence in lower mammals (Flügel et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that they protect the fovea against extreme temperature changes and suggest that they influence the position of the fovea by altering the thickness of the choroid. (Parver et al 1980(Parver et al , 1983Bill 1985;Bill and Nilsson 1985;Parver 1991;Zagvazdin et al 1996;Cuthbertson et al 1997;Poukens et al 1998;Shih et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…7,12 Because of the concealed position of the pterygopalatine ganglion, however, far less is known both functionally and structurally of the facial nerve pathway than of the oculomotor pathway. This applies especially to birds, a major animal model in experimental ophthalmology, in which the pterygopalatine ganglion consists of a chain of interconnected microganglia [13][14][15][16] that reside deep in the nasal side of the orbit, between the sclera and the Harderian gland, an accessory lacrimal gland found in many species. 17,18 Hence, experimental manipulation of this pathway appears to require a quite invasive technique.…”
mentioning
confidence: 99%